2010
DOI: 10.3171/2009.11.peds09341
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic stunned myocardium after acute hydrocephalus

Abstract: Neurogenic stunned myocardium (NSM) is a syndrome of cardiac stunning after a neurological insult. It is commonly observed after aneurysmal subarachnoid hemorrhage but is increasingly being reported after other neurological events. The underlying mechanism of NSM is believed to be a hypothalamic-mediated sympathetic surge causing weakened cardiac contractility and even direct cardiac myocyte damage. The authors report 2 cases of NSM in pediatric patients after acute hydrocephalus. Both patients experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…According to monkey experimental model findings, myocardial sympathetic denervation, as opposed to vagotomy or bilateral adrenalectomy, completely eliminates the phenomenon of subendocardial necrosis [3], which confirms the role of local release of catecholamines from nerve endings. Moreover, animal studies demonstrate a correlation between concentrations of troponin I, CK-MB and catecholamines in plasma [13]. The theory described above seems to be confirmed by a small-scale study involving patients with subarachnoid haemorrhage in whom the administration of propranolol and phentolamine had cardioprotective effects [13].…”
Section: Etiopathogenesissupporting
confidence: 49%
See 3 more Smart Citations
“…According to monkey experimental model findings, myocardial sympathetic denervation, as opposed to vagotomy or bilateral adrenalectomy, completely eliminates the phenomenon of subendocardial necrosis [3], which confirms the role of local release of catecholamines from nerve endings. Moreover, animal studies demonstrate a correlation between concentrations of troponin I, CK-MB and catecholamines in plasma [13]. The theory described above seems to be confirmed by a small-scale study involving patients with subarachnoid haemorrhage in whom the administration of propranolol and phentolamine had cardioprotective effects [13].…”
Section: Etiopathogenesissupporting
confidence: 49%
“…The theory described above seems to be confirmed by a small-scale study involving patients with subarachnoid haemorrhage in whom the administration of propranolol and phentolamine had cardioprotective effects [13]. Likewise, another randomized study of 114 patients with acute CNS damage has demonstrated that the immediate initiation of atenolol treatment reduced the severity of myocardial necrosis determined by increased CK-MB concentrations [13]. The question arises whether catecholamines commonly used in such cases can exert iatrogenic effects.…”
Section: Etiopathogenesismentioning
confidence: 53%
See 2 more Smart Citations
“…4,11,15) However, TCM occurs more frequently than NPE in the absence of a posterior fossa lesion, 18,19) and the relationship between aneurysm location and TCM has been studied less frequently. The possible anatomical difference in a causative brain lesion between NPE and TCM suggests that a sudden rise in serum catecholamine level induces TCM, whereas both rise in the serum catecholamine level and mechanical compression of the medulla are required for induction of NPE.…”
mentioning
confidence: 99%